Tax Policy and Entrepreneurship in the Presence of Asymmetric Information in Capital Markets - Clemens Fuest; Bernd Huber; Philipp Tillessen (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper considers the implications of asymmetric information in capital markets for entrepreneurial entry and tax policy. In many countries, governments subsidize the creation of new firms. One possible justification for these subsidies is that capital markets for the financing of new firms do not function properly. We analyse this issue by assuming that entrepreneurs need outside financing for their projects and know more about the quality of their projects than outside investors. Entrepreneurs have the choice between carrying out their entrepreneurial projects or working as an employee. It turns out that asymmetric information in capital markets leads to too much rather than too little entrepreneurial entry. Therefore, the ptimal tax policy should discourage rather than subsidize entrepreneurial entry. We also nalyse the welfare effects of project screening and show that there is too much screening. Our policy conclusion is that subsidies for the foundation of firms must be based on reasons other than informational asymmetries in capital markets.
Keywords: 330